2020
DOI: 10.1039/d0ta07232j
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Zn dendrite growth by molecular layer deposition to enable long-life and deeply rechargeable aqueous Zn anodes

Abstract: Rechargeable zinc-ion batteries (ZIBs) in mild/neutral aqueous electrolytes are promising for large-scale energy storage applications due to their merits of high capacity, intrinsic high safety, low cost and environmental benignity....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 43 publications
0
60
0
Order By: Relevance
“…13 c), and protected the Zn anode. In addition, Liu et al [ 106 ] synthesized alucone (an inorganic–organic hybrid coating) using a molecular deposition technique. The coating improved the wettability of the Zn anode and led to the uniform deposition of Zn (Fig.…”
Section: Surface Modification Of Zn Anodementioning
confidence: 99%
“…13 c), and protected the Zn anode. In addition, Liu et al [ 106 ] synthesized alucone (an inorganic–organic hybrid coating) using a molecular deposition technique. The coating improved the wettability of the Zn anode and led to the uniform deposition of Zn (Fig.…”
Section: Surface Modification Of Zn Anodementioning
confidence: 99%
“…It reveals the coordination between carbonyl oxygen atoms with Zn 2+ , which can be stronger when polyamide structure collapse over cycling. Molecular layer deposition was employed to produce alucone coating on Zn foil [64] . The nanoscale alucone layer can improve wettability and hence benefit the interface kinetics.…”
Section: Artificial Sei For Zn Anodementioning
confidence: 99%
“…Secondly, the hybrid films could also be employed as surface coating layers to address liquid-solid and solid-solid interface issues in conventional liquid-based LIBs, solid-state LIBs, and next-generation batteries (e.g., Na, K, and Zn-ion). This surface-engineering approach has been widely demonstrated using alucone, a mature MLD material, in a broad range of applications, such as Si anode (Piper et al, 2014), Li metal (Zhao et al, 2018a), Na metal (Zhao et al, 2017), Zn metal (He and Liu, 2020), Na cathode (Kaliyappan et al, 2020), and many others (Zhao et al, 2021). Compared to insitu formed SEI, the MLD coating, as an artificial SEI on the electrode, become ion and electron conductive upon contact with charge carriers (e.g., Li-ion, Na-ion), possess better mechanical stability and interfacial structure integrity over repeated cycling, and prevent further side reactions between the electrode and electrolyte.…”
Section: Other New Mld Thin Films Promising For Rechargeable Batteriesmentioning
confidence: 99%
“…The incorporation of organic fragments technically opens unlimited possibilities for engineering the structure of metalcone at the molecular level and tailoring their mechanical, electrical, optical, and electrochemical properties for energy storage and conversion systems (Sundberg and Karppinen, 2014;Meng, 2017). For example, MLD alucone has been applied as a flexible surface coating layer on the various anode (Si, SnO 2 , Li/Na/Zn metals) and cathode in rechargeable Li, Na, and Zn batteries (Piper et al, 2014;Zhao et al, 2018a;He and Liu, 2020), and been found to outperform its ALD Al 2 O 3 counterpart in stabilizing the electrode-electrolyte interfaces owing to the added benefits from the organic fragment. For example, alucone coating, deposited by using trimethylaluminum (TMA) and glycerol (GL) at 140°C, was found to improve the cycling stability, rate, and Coulombic efficiency of nano-Si composite electrodes (Piper et al, 2014).…”
Section: Introductionmentioning
confidence: 99%